Inhibiting Factors of Land Suitability for Piper nigrum L. in a Hilly Area of Tirtomoyo District, Central Java - Mujiyo Mujiyo; Sutarno Sutarno; Suwarto Suwarto; R Budiono; novi rahmawati sutopo (JOURNAL OF TROPICAL SOILS, 2020)
Pepper (Piper nigrum L.) has a high selling value. The price of pepper in the domestic or international market that is always high can be a great opportunity to increase farmers’ income. Tirtomoyo District is dominated by hilly areas with common soil types of Litosol and Latosol. As one of the efforts to develop the regional economic rate, especially in hilly areas, pepper cultivation can be a solution offered by the agricultural sector. The study was conducted using an explorative descriptive survey method consisting of field observation and laboratory analysis. The analytical unit used was Land Map Unit (LMU) obtained from soil map. The sampling sites were selected using purposive sampling method according to the research objectives and representing the study area. The results show that the actual land suitability for pepper in Tirtomoyo District is marginally suitable (S3) for all LMU. The main limiting factors are water availability and nutrient availability, thus the Tirtomoyo district still have potency for pepper cultivation by applying some improvement measures such as fertilization, irrigation, organic material addition, and cover crop planting.